2021
DOI: 10.1038/s41598-021-89471-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among sea urchins in response to food cues

Abstract: Interaction among sea urchins remains largely uninvestigated, although the aggregation of sea urchins is common. In the present study, 1, 15 and 30 sea urchins Strongylocentrotus intermedius (11.06 ± 0.99 mm in test diameter) were placed in a 1 m2 circular tank, respectively. Movement behaviors were recorded for 12 min to investigate potential interactions among sea urchins. After the 12-min control period, we added food cues into the tank and recorded the changes in sea urchins’ behaviors. For the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Spreading out from the aggregations is an important behavioral process for sea urchins and sea cucumbers to reduce the competition within groups 52 , 53 . We thus calculated the distance of the animals from the center of the tank at the beginning and the end of the experiment to analyze their centrifugal movement.…”
Section: Methodsmentioning
confidence: 99%
“…Spreading out from the aggregations is an important behavioral process for sea urchins and sea cucumbers to reduce the competition within groups 52 , 53 . We thus calculated the distance of the animals from the center of the tank at the beginning and the end of the experiment to analyze their centrifugal movement.…”
Section: Methodsmentioning
confidence: 99%
“…The duration and frequency of three states were recorded, and each state was taken as a sample for data analysis. Movement speed (v) and displacement (d) of sea cucumber during three states were calculated as follows [29]:…”
Section: Experiments 1: Movement Pattern Of a Japonicus Without Food Cuementioning
confidence: 99%
“…We consistently found that interactions seriously hamper the movement of S . intermedius 24 . Thus, it is reasonable to hypothesize that eliminating interactions in multi-layer culture probably further improves important traits of sea urchins.…”
Section: Introductionmentioning
confidence: 99%